Penerapan Pajak Penghasilan Pasal 23 Terhadap Kepatuhan Wajib Pajak - Fransiska, Bella; Diah Widajantie, Tituk (Economic Reviews Journal, 2024)
Compliance with Income Tax (PPh) 23 among companies varies greatly. Some companies comply, while others still face challenges in adhering to the regulations. Factors such as a lack of understanding of the regulations, complicated administration, or the intent to evade taxes often lead to non- compliance. As much as 82.5% of the realized state revenue in the third quarter of 2019 came from taxes. Income Tax and Value Added Tax were the largest contributors to the total tax revenue collected by the government. This article aims to identify the criteria that determine whether a company can be considered compliant with its tax obligations. This study uses qualitative research with descriptive data collection and focuses on the context provided by individuals or groups involved in the study. The focus of this research explains the criteria for companies that have complied with their tax obligations. The results of this study indicate that there are several tax compliance criteria according to Law Number 6 of 1983 concerning General Provisions and Tax Procedures, including timely registration, meaning that the taxpayer or the company registers itself after meeting the requirements set by the tax authorities and then starts its business.